Legal certainty of ruling of the consumer dispute resolution agency (BPSK) number: 20/pts/bpsk/x/2022 regarding objections of pt. Bank sumsel babel - Muslim, Muslim; Hayatuddin, Khalisah; Kasra, Helwan (Universitas Muhammadiyah Sumatera Utara, 2024)
Consumer Dispute Resolution Agency (BPSK) in Level II Regions to resolve consumer disputes through out-of-court channels, namely by mediation, arbitration or conciliation, and dispute resolution can be done quickly, easily and cheaply and BPSK decisions are final and binding, if accepted by both parties. Even though the BPSK decision is final and binding, an objection can be submitted to the Court. This research aims to analyze 1. What are the duties and authorities of the Palembang City Consumer Dispute Resolution Agency (BPSK) in resolving consumer disputes from a civil law perspective 2. What is the Legal Certainty of the Decisions of the Consumer Dispute Resolution Agency (BPSK) Number: 20/PTS / BPSK /X/ 2022 against PT. Bank SumselBabel. Normative research methods with statutory, conceptual and case approaches. The research results show that BPSK is passive in carrying out its duties and authority and acts when there are complaints from consumers. The BPSK decision does not provide legal certainty for consumers because after PT. Bank SumselBabel submitted an objection to the BPSK decision to the Court before 14 days and based on Court Decision number: 298 / Pdt.Sus-BPSK / 2022 /PN Plg canceled the BPSK decision Number: 20/PTS / BPSK /X/2022. This is due to the existence of contradictions between one rule and another relating to BPSK decisions. It is necessary to revise clear regulations regarding consumer protection so that they become a strong legal umbrella for BPSK decisions.